Development of an Android-Based Application for Family Planning Education and Consultation (SIDUTA KB) - Vika Rifti Ananditya; Muhammad Azinar (International Journal of Regional Innovation, 2021)
In suppressing the rate of population growth, the government seeks to optimize the Family Planning (KB) program. Miroto Public Health Center is a health center in the Central Semarang District which experienced a decrease of 13.4% of new family planning memberships. The decline was caused by the increase in the number of births, the delay in contraceptive services and the soaring unmet need during the pandemic. To support the role of cadres in providing socialization easily without having to meet during this pandemic, a Family Planning Education and Consultation System (SIDUTA KB) was created. Methods: This study uses Research and Development (RnD) which refers to the Sugiyono model with limited trials. The research data analysis technique is descriptive analysis and the data collected consists of qualitative and quantitative. Results: In this study, design validation was carried out through media expert tests with a percentage score of 83.55% (5 experts), material experts at 81.11% (3 experts), and users by 86.72% (73 users). Conclusion: SIDUTA KB makes it easy for users to find educational content about family planning programs, conduct consultations, and choose Miroto Health Center facilities or services related to the family planning program.